Determination of specific and non-specific standardization parameters for ethanol extract of purple leaves (Graptophyllum pictum (L) Griff ) - Rivani Tampang; Syafika Alaydrus; Niluh Puspita Dewi; Joni Tandi (Postgraduate, University of Mataram, 2024)
this study aims to determine the standardization of specific parameters (organoleptic and chemical content) and non-specific parameters (ash content, water content, drying loss, heavy metal contamination, Yeast Mold Number (AKK), microbial contamination / Total Plate Count (ALT)). The results showed that the specific parameters of the organoleptic properties of 96% ethanol extract of purple leaves (Grapthophyllum pictum (L) Griff) were black, shaped like a paste, a distinctive purple leaf odor and a bitter taste. The results of phytochemical screening of 96% purple leaf ethanol extract contained alkaloids, flavonoids, and tannins. However, the saponin test was negative for saponins. Non-specific parameters of 96% ethanol extract of cherry leaves were water content of 5.96%, total ash content of 16.86%, drying loss of 17.26%, heavy metals As and Cd were not detected, the presence of metals in Pb was 0.12 mg / kg, microbial contamination (Alt) and yeast mold numbers (Akk) were not found colonies. Based on these results, it can be concluded that the standardization test of specific and non-specific parameters, the ethanol extract of purple leaves has met the quality standards of simple drugs.